(untitled) (SCIENCE TIME JOURNAL, 2026)
This study examines character classification in literary studies through the lens of dual character relationships. It argues that characters should be analyzed not only as individual entities but as relational constructs that shape narrative meaning. Drawing on interdisciplinary approaches and examples from American and British literature, the research demonstrates that contrasting and complementary character pairs contribute significantly to narrative identity, thematic development, and psychological depth. The findings suggest that a relational model of character classification provides a more comprehensive framework for understanding literary narratives.